Definitely, you can approach it via @Incredible Mind's Method but I would like to share another method.

We can proceed by using Euler's Formula
\[e^{ix} = \cos x + i\sin x\]
\[\Rightarrow \cos x = \frac{e^{ix}+e^{-ix}}{2}\]

Thus, setting \(x= \frac{2k\pi}{n}\), we can compute the sum as follows:

\[\begin{eqnarray}
\sum_{k=1}^{n-1} (n-k)\cos \frac{2k\pi}{n} & = & \sum_{k=1}^{n-1} (n-k) \frac{e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}}{2} \\
& = & \frac{n}{2} \sum_{k=1}^{n-1} \left(e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) - \frac{1}{2} \sum_{k=1}^{n-1} k \left( e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) \\
& = & \frac{n}{2} \sum_{k=1}^{n-1} \left(e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) - \frac{1}{2} \sum_{k=1}^{n-1} k \left( e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) \\
\end{eqnarray}\]
Now that above series (the first sum) is a simple Geometric Expansion and the second one can be obtained by differentiating the first one.
(Hint : \(\sum_{r=1}^{n} x^r = \frac{x(x^n-1)}{x-1}\) and \(\sum_{r=1}^{n} rx^r = \frac{x+(nx-n-1)x^{n+1}}{(x-1)^2}\))

Finally, it evaluates to
\[\sum_{k=1}^{n-1} (n-k)\cos \frac{2k\pi}{n} = \frac{n}{2}\left(-2\right)-\frac{1}{2}\left(-n\right) = -\frac{n}{2}\]
(I urge the reader to verify the above result themselves)

\(\textbf{EDIT : }\) A general approach for finding the sum of series of type \(\sum_{k=1}^n kr^k\) (doesn't involves differentiation)

Let \[S_n = \sum_{k=1}^n kr^k = r + 2r^2 + 3r^3 + \ldots + nr^n\]

To distinguish the 2 approaches, you should explain that the second summation can be obtained by methods other than differentiation, especially since Omkar said he doesn't know differentiation.

This is a useful formula to be aware of, to sum scenarios like this.

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestDefinitely, you can approach it via @Incredible Mind's Method but I would like to share another method.

We can proceed by using Euler's Formula \[e^{ix} = \cos x + i\sin x\] \[\Rightarrow \cos x = \frac{e^{ix}+e^{-ix}}{2}\]

Thus, setting \(x= \frac{2k\pi}{n}\), we can compute the sum as follows:

\[\begin{eqnarray} \sum_{k=1}^{n-1} (n-k)\cos \frac{2k\pi}{n} & = & \sum_{k=1}^{n-1} (n-k) \frac{e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}}{2} \\ & = & \frac{n}{2} \sum_{k=1}^{n-1} \left(e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) - \frac{1}{2} \sum_{k=1}^{n-1} k \left( e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) \\ & = & \frac{n}{2} \sum_{k=1}^{n-1} \left(e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) - \frac{1}{2} \sum_{k=1}^{n-1} k \left( e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) \\ \end{eqnarray}\] Now that above series (the first sum) is a simple Geometric Expansion and the second one can be obtained by differentiating the first one. (Hint : \(\sum_{r=1}^{n} x^r = \frac{x(x^n-1)}{x-1}\) and \(\sum_{r=1}^{n} rx^r = \frac{x+(nx-n-1)x^{n+1}}{(x-1)^2}\))

Finally, it evaluates to \[\sum_{k=1}^{n-1} (n-k)\cos \frac{2k\pi}{n} = \frac{n}{2}\left(-2\right)-\frac{1}{2}\left(-n\right) = -\frac{n}{2}\] (I urge the reader to verify the above result themselves)

\(\textbf{EDIT : }\) A general approach for finding the sum of series of type \(\sum_{k=1}^n kr^k\) (doesn't involves differentiation)

Let \[S_n = \sum_{k=1}^n kr^k = r + 2r^2 + 3r^3 + \ldots + nr^n\]

Then observing closely

\[\begin{eqnarray} S_n & = & r + 2r^2 + 3r^3 + \ldots + nr^n \\ rS_n & = & \qquad r^2 + 2r^3 + \ldots + (n-1)r^n + nr^{n+1} \end{eqnarray}\]

Subtracting the second series from second one, we get

\[(1-r)S_n = (r + r^2 + r^3 + \ldots + r^n) - nr^{n+1} = \frac{r(1-r^n)}{1-r}-nr^{n+1}\] \[\Rightarrow S_n =\frac{r(1-r^n)}{(1-r)^2}-\frac{nr^{n+1}}{1-r}\]

I hope that helps \(:)\)

Log in to reply

To distinguish the 2 approaches, you should explain that the second summation can be obtained by methods other than differentiation, especially since Omkar said he doesn't know differentiation.

This is a useful formula to be aware of, to sum scenarios like this.

Log in to reply

ok sir, I'll edit my solution, right now. \(:)\)

Log in to reply

Oh okay. Thanks!

Log in to reply

split it .then 1st can be known by using complex numbers.2nd sum from differentiation of

S=sinx+sin2x+sin3x...sin(n-1)x.........use the sum formula .then diff. w.r.t x both sides.then sub x=2pi/n.

i cannot type because i dont know LATEX

Log in to reply

Oh okay, but I don't know about differentiation. Is there any other method? I think complex numbers come handy.

Log in to reply

But there too you need to use differentiation.

Anyways, I'll definitely think of some another approach which doesn't involves differentiation.

Log in to reply